The mismeasure of man - Gould, Stephen Jay (W. W. Norton & Company, 1996)
How smart are you? If that question doesn't spark a dozen more questions in your mind (like "What do you mean by 'smart,'" "How do I measure it," and "Who's asking?"), then The Mismeasure of Man, Stephen Jay Gould's masterful demolition of the IQ industry, should be required reading. Gould's brilliant, funny, engaging prose dissects the motivations behind those who would judge intelligence, and hence worth, by cranial size, convolutions, or score on extremely narrow tests. How did scientists decide that intelligence was unipolar and quantifiable, and why did the standard keep changing over time? Gould's answer is clear and simple: power maintains itself. European men of the 19th century, even before Darwin, saw themselves as the pinnacle of creation and sought to prove this assertion through hard measurement. When one measure was found to place members of some "inferior" group such as women or Southeast Asians over the supposedly rightful champions, it would be discarded and replaced with a new, more comfortable measure. The 20th-century obsession with numbers led to the institutionalization of IQ testing and subsequent assignment to work (and rewards) commensurate with the score, shown by Gould to be not simply misguided--for surely intelligence is multifactorial--but also regressive, creating a feedback loop rewarding the rich and powerful. The revised edition includes a scathing critique of Herrnstein and Murray's The Bell Curve, taking them to task for rehashing old arguments to exploit a new political wave of uncaring and belt tightening. It might not make you any smarter, but The Mismeasure of Man will certainly make you think